CONTENT STRUCTURE OF SELF-EDUCATION EDUCATION IN COLLEGE STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the contextual structure of colldges' atudets upbringing of self-esteem and the main components: cognotive, emotional-values and self-evolation auitude towards itself are studied.
Keywords: structure; self-esteem; euitude toward itself; self-knowledge; self-evolation